Power Quality Considerations for Distributed Generation Integration in the Nigerian Distribution Network Using NEPLAN Software - Alayande, Akintunde S.; Owoicho, O. D.; Somefun, Tobiloba Emmanuel; Olowoleni, Joseph; Okakwu, Ignatius K.; Abdulkareem, Ademola (International Journal of Energy Economics and Policy, 2021)
Power quality studies are increasingly becoming a toast of major researchers as it is now a major factor utilized in determining the overall efficiency of an electrical power system. Voltage profile and power loss are significant pointers to the quality of power and as such, distributed generation comes into play since it offers competitive advantages over the traditional grid interconnected system. In this study, therefore, an attempt is made in comparing the voltage profile of the traditional grid system of a typical distribution network and with that incorporated with the distributed generation, using real data of a practical system of the Nigeria distribution company. The conceptual framework as well as the mathematical formulations required for the study are presented. The data are, then, simulated using a NEPLAN software. The results obtained from the simulations for power losses in both scenarios are examined. The results obtained clearly showed that there is a significant reduction in power losses and a substantial improvement in the voltage profile of an embedded generation in-feed scheme in comparison with the conventional grid in-feed. Keywords: Distributed Generation, Power Quality, Voltage Profile, Grid in-feed, Transmission Losses JEL Classifications: C63, L94, L98, Q48 DOI: https://doi.org/10.32479/ijeep.11145